Improving Students’ Reading Comprehension through GIST (Generating Interaction between Schemata and Text) Strategy - Elany Agnescia; Joko Sutrisno AB; Eny Dwi Marcela (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2022)
This research aimed to improve students’ learning activities and their reading comprehension by using Generating Interaction between Schemata and Text (GIST) strategy. In this research, the researcher used Classroom Action Research as the method of this research. This research implemented Generating Interaction between Schemata and Text (GIST) in 2 cycles with 3 meetings in each cycle. The sample of this research was in one class with 31 students. The test used in this research was 30 multiple choice questions. The average score of students’ activities based on the observation sheet in cycle I obtained range 7 which categorized as quite active and increased to be 7.7 in cycle II which categorized as active. The average score of students’ reading comprehension in cycle I was 68.46 and increased to be 79.11 in cycle II. The percentage of the students’ reading comprehension test in cycle I who passed Minimum Mastery Criteria was 45.16% students passed the KKM and in cycle II the result increased to be 83.87% students passed KKM. From the learning activities and test result, the researcher concluded that there was an improvement in students' learning activities and their reading comprehension by implementing Generating Interaction between Schemata and Text (GIST) strategy at the eighth-grade students of SMP Negeri 21 Bandar Lampung in the academic year of 2021/2022.